2018
DOI: 10.1371/journal.pone.0203140
|View full text |Cite
|
Sign up to set email alerts
|

How do housing prices affect consumption in China? New evidence from a continuous wavelet analysis

Abstract: In this paper, we revisit the relationship between housing prices and consumption in China by using a continuous wavelet analysis. This method provides an insight into the dynamic nexus in both time and frequency domains. In general, Empirical results show that there is a positive relationship between the two series in China, although it varies across time and frequencies. First, we find that disposable income is the core factor which affects both consumption and housing prices in China. Second, housing prices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…[ 15 ] study ageing and house prices in Korea again in a panel regression framework but results between rural and urban areas are mixed. [ 16 ] find that house prices in China have a weak wealth effect on consumption but results vary across horizons. None of the papers cited above focus on long run ageing risk, measured by cointegration relation between rural area ageing and house prices.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] study ageing and house prices in Korea again in a panel regression framework but results between rural and urban areas are mixed. [ 16 ] find that house prices in China have a weak wealth effect on consumption but results vary across horizons. None of the papers cited above focus on long run ageing risk, measured by cointegration relation between rural area ageing and house prices.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found that such rapid housing appreciation has affected individuals and households enormously. The rise in housing prices has been found to tighten household consumption (Su, Yin and Tao, 2018;Waxman et al, 2019), reduce female labor force participation (Fu, Liao and Zhang, 2016), increase marriage age (Wrenn, Yi and Zhang, 2019), and raise the probability of inter-generational co-residence (Li and Wu, 2019), among other things. Yet little is known about the health consequences of the rapid growth in housing prices.…”
Section: Introductionmentioning
confidence: 99%
“…To address the potential periodicity, time-frequency comovement, and lead-lag effects of non-stationary long-term time series, wavelet analysis is a mathematically basic tool to discover how to approximate time series to a certain frequency band within a certain time period simultaneously, which could optimally describe the occurrence of transient events, and well adapt to conditions where the amplitude of the response varies significantly in non-stationary time series (Steel and Lange, 2007;Cloern and Jassby, 2010;Rhif et al, 2019). As the extended usage of wavelet transform, wavelet coherence (Maraun and Kurths, 2004;Su et al, 2018Su et al, , 2019 and phase difference (Aguiar-Conraria and Soares, 2011) can be utilized to recognize whether two time series are quantitatively linked by a certain correlation, even causality relationship. Kogovšek et al (2010) have applied continuous wavelet transform to investigate the long-term fluctuation of time series of jellyfish abundance in the past 200 years and further confirmed a major and minor period of its proliferation.…”
Section: Introductionmentioning
confidence: 99%